Segmental aneuploidy and the genetic gross structure of the Drosophila genome. - Lindsley, D.L.; Sandler, L.; Baker, B.S.; Carpenter, A.T.C.; Denell, R.E.; Hall, J.C.; Jacobs, P.A.; Miklos, G.L.G.; Davis, B.K.; Gethmann, R.C.; Hardy, R.W.; Hessler, A.Y.; et al. (Genetics, 1972)
By combining elements of two Y-autosome translocations with displaced autosomal breakpoints, it is possible to produce zygotes heterozygous for a deficiency for the region between the breakpoints, and also, as a complementary product, zygotes carrying a duplication for precisely the same region. A set of Y-autosome translocations with appropriately positioned breakpoints, therefore, can in principle be used to generate a non-overlapping set of deficiencies and duplications for the entire autosomal complement.-Using this method, we have succeeded in examining segmental aneuploids for 85% of chromosomes 2 and 3 in order to assess the effects of aneuploidy and to determine the number and location of dosage-sensitive loci in the Drosophila genome (Figure 5). Combining our data with previously reported results on the synthesis of Drosophila aneuploids (see Lindsley and Grell 1968), the following generalities emerge.-1. The X chromosome contains no triplo-lethal loci, few or no haplo-lethal loci, at least seven Minute loci, one hyperploid-sensitive locus, and one locus that is both triplo-abnormal and haplo-abnormal. 2. Chromosome 2 contains no triplo-lethal loci, few or no haplo-lethal loci, at least 17 Minute loci, and at least four other haplo-abnormal loci. 3. Chromosome 3 contains one triplo-lethal locus that is also haplo-lethal, few or no other haplo-lethal loci, at least 16 Minute loci, and at least six other haplo-abnormal loci. 4. Chromosome 4 contains no triplo-lethal loci, no haplo-lethal loci, one Minute locus, and no other haplo-abnormal loci.-Thus, the Drosophila genome contains 57 loci, aneuploidy for which leads to a recognizable effect on the organism: one of these is triplo-lethal and haplo-lethal, one is triplo-abnormal and haplo-abnormal, one is hyperploid-sensitive, ten are haplo-abnormal, 41 are Minutes, and three are either haplo-lethals or Minutes. Because of the paucity of aneuploid-lethal loci, it may be concluded that the deleterious effects of aneuploidy are mostly the consequence of the additive effects of genes that are slightly sensitive to abnormal dosage. Moreover, except for the single triplo-lethal locus, the effects of hyperploidy are much less pronounced than those of the corresponding hypoploidy.